A Systematic Approach for Dissolution Enhancement of Felodipine using Hydrophilic Polymers for Solid Dispersion Preparation - Butani, Dr. Shital (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the study was to systematically explore hydrophilic polymers as carrier for dissolution enhancement using central composite design of experiment. Materials and Methods: Felodipine was chosen as drug prototype for this study. Influence of formulation and processing parameters such as drug: Polymer ratio, solid content of feed solution, inlet temperature, and aspirator percentage was studied on evaluation parameters such as percent yield and drug release of solid dispersions using a 34 central composite design of experiment. Effect of incorporation of surface active agent like polysorbate 80 on further increasing the in vitro dissolution was also studied. Results and Discussion: Conversion of crystalline drug into amorphous form in solid dispersions was confirmed by Differential scanning study and X-ray diffraction studies. In vitro dissolution study showed 55–60 fold increase in drug release within 60 min for spray dried solid dispersion as compared to untreated drug. In vitro drug release was enhanced to 64–70 fold as compared to drug when polysorbate 80 (Tween 80) was used as co-carrier for solid dispersion preparation. On basis of preliminary comparative dissolution trials PVP K 30 was selected as suitable carrier polymer for further trials. Outcome of design of experiment trials indicated that drug: Polymer ratio has maximum influence on drug dissolution from solid dispersions. Higher the ratio, more the drug release. Process yield is mainly dependent on feed solid concentration and aspirator speed. Low solid content of spraying solution and higher aspirator speed is required to get good process yield. Conclusion: The current study demonstrates that PVP K 30 is a suitable carrier polymer to generate stable solid dispersions to enhance drug dissolution using spray drying technology. Selection of appropriate formulation and processing conditions such as drug: polymer ratio, inlet temperature, aspirator speed and solid content of feed solution determines the quality, and performance of the solid dispersions.